Sociodemographic factors of mental health literacy among housewives living in low cost apartments in Puchong, Selangor, Malaysia - Mohamed Hussain, Siti Nor Amirah; H., Husna; Azhar, Muhamad Afnan; Ismail, Suriani; Mohd Nazan, Ahmad Iqmer Nashriq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Evaluation of mental health literacy is important in assisting the development of intervention and policies toward preventing mental health problems. This study aims to explore mental health literacy and its socio-demographic predictors in a group of housewives living in low-cost apartments in Selangor, Malaysia. Methods: A Malay version of the self-administered Mental Health Literacy Scale (MHLS) was used in this cross-sectional study. Age, ethnicity, religion, educational level and family income were tested using one-way ANOVA and independent t-test. Result: A total of 103 eligible respondents participated in the study. Most respondents were from the age group of 30 and above, from the Malay ethnic group, Muslims, had formal education up to secondary level with a monthly family income below RM4000 (USD980). The overall mean (sd) mental health literacy score was low 106.65 (11.21) and was significantly associated with ethnicity, religion, educational level and family income (p>0.05). Conclusion: Mental health literacy scores were low and showed variations within sociodemographic groups.